Supply Chain Management Based on SAP Systems - Knolmayer, G.F. (Springer, 2017)
Supply Chain Management (SCM) is not a buzzword like many others in management and IT - it is here to stay. "Megatrends" such as globalization and increasing specialization result in a complex division of labor at national and international levels. Lean and agile supply chains have become a major management target, and the interorganizational coordination of business processes has become highly relevant. The complexity of today's supply chains cannot be mastered without the support of powerful information systems. SAP has established itself as the market leader in this type of IT systems. The book describes SCM using a pyramidal framework and relates it to the SAP SCM Solution Map. Desired features of IT support for SCM are formulated, and the extent to which SAP systems provide these features is shown. We describe the functionalities of SAP APO™ in detail, present case studies on implementing and running SAP SCM™ systems, and discuss SCM aspects of the new SAP Business ByDesign™ approach.